Effect of Liuzijue on Pulmonary Function of Patients with Ischemic Stroke and Hemiplegia - CHEN Yannan; ZHANG Hongxin; DENG Lijin; WENG Meihua; HU Jingwen; ZHOU Hongjuan; YOU Shijing; CHEN Jinxiu (康复学报)
ObjectiveTo observe the effect of respiratory training with Liuzijue on pulmonary function, activities of daily living and quality of life in patients with ischemic stroke and hemiplegia.MethodsA total of 76 patients with ischemic stroke and hemiplegia who were hospitalized in the Second Affiliated Hospital of Fujian Medical University and the Jinjiang Hospital of Traditional Chinese Medicine Affiliated to Fujian University of Traditional Chinese Medicine were recruited from March to September 2019. The patients were divided into control group (n=38) and experimental group (n=38) using a random number table method and according to the order of admission. The control group received routine treatment, nursing care, and early rehabilitation training; in addition to these interventions, the experimental group received Liuzijue respiratory training, and the patients were instructed with nasal inspiration and mouth expiration method, and the expiration was carried out in accordance with the Liuzijue sequence of "xu" "he" "hu" "si" "chui" "xi" 30 min/time, once a day, 5 days a week, lasting for 12 weeks. The forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), peak expiratory flow (PEF) rate and maximum voluntary ventilation (MVV) volume of the two groups were evaluated by portable pulmonary function meter before and after the intervention; the modified Barthel index (MBI) was used to evaluate activities of daily living; the stroke impact scale (SIS) was used to evaluate the quality of life.ResultsBefore the intervention, there was no statistical difference in the FVC, FEV1, PEF, MVV, MBI, and SIS scores between the two groups (P>0.05). After 12 weeks of intervention, the scores of the FVC, FEV1, PEF, MVV, MBI, SIS in both groups improved significantly compared with those before intervention, and the differences were statistically significant (P<0.001). After the intervention, the pulmonary function indexes of FVC, FEV1, PEF, MVV of the experimental group were (2.63±0.68) L, (2.33±0.68) L, (4.49±1.39) L/s, (44.08±13.89) L/min respectively, which were better than those in the control group (2.31±0.50) L, (2.03±0.48) L, (3.79±1.46) L/s, (34.74±15.21) L/min, and the differences were statistically significant (P<0.05). The MBI score of the experimental group was (80.11±17.19), which was greater than that of the control group (73.67±13.94), and the difference was statistically significant (P<0.05). The SIS score of the experimental group after the intervention was (565.14±99.93), which was greater than that of the control group (517.19±74.24), and the difference was statistically significant (P<0.05).ConclusionsLiuzijue respiratory training could effectively improve the pulmonary function of patients with ischemic stroke and hemiplegia, and contribute to the recovery of their activities of daily living and improve their quality of life.